Effect of premature weaning on litter performance and weaning-to-estrus interval in sows (Semiárida, 2020)
The aim of the present study was to evaluate the possibility of increasing the reproductive performance of the sow by reducing the normal period, without effect upon the potential production of the litter, Primiparaus sows with their litter were maintained under confinement and divided into 3 treatments with replications ach within a randomized blocks design Statistical analysis were performed through analysis of variance and test of Tukey. Treatment one (T1) consisted of a control with suckling period of 56 day. T2: 42 days and T3: 35 days. AU the 50WS received a feeding level of 1 of Iiveweight plus 300 g, on dry matter basis per suckling pig, once a day during the morning; the pigs were fed with a commercial prestarter feedsluff "ad libitum" from the 141h day lite. The parameters measured in this study were: liveweight al the end of lactation and date of first estrus alter weaning in the sows. Mean Iiveweight gain in pigs was  different (P>0.05), (T1: 13.44 T2: 13.38, T3: 13.74 Kg), differences in pre-starter intake were highly significant (P
Keywords: Prematures weaning; Primiparaus sows; Weaning-estrus interval